2018
DOI: 10.21451/1984-3143-ar2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of scrotum bipartition in sheep in the Paraiba backwoods, Brazil

Abstract: Goats and sheep have morphological characteristics for adaptation to desert and semiarid regions. The appearance of scrotum division known as scrotum bipartition has already been reported in goats. This anatomy increases the surface of each testicle exposed to environmental temperature, favoring heat dissipation and improving reproductive efficiency. Considering that there are already studies on the goat species demonstrating the presence of this characteristic as an influence on reproductive parameters, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In the present work, the tests performed with 2% chlorhexidine also indicated satisfactory decontamination within 15 seconds in all tested cones. Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present work, the tests performed with 2% chlorhexidine also indicated satisfactory decontamination within 15 seconds in all tested cones. Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussioncontrasting
confidence: 99%
“…The same results were found in the present study, during the experiment using 2% sodium hypochlorite. Nevertheless, a previous work 20 showed that decontamination only took place within one minute.…”
Section: Discussionmentioning
confidence: 96%